THE IMPLEMENTATION OF DAKON MATHEMATICS (DAKOTA) LEARNING MEDIA WITH DISCOVERY LEARNING METHOD: THE IMPLEMENTATION OF DAKON MATHEMATICS (DAKOTA) LEARNING MEDIA WITH DISCOVERY LEARNING METHOD - Lestari, Fitria; Efendi, Deni; Hardianti, Desrina (Fakultas Tarbiyah dan Ilmu Keguran IAIN Metro, 2024)
The learning faced by students is teacher-centered learning. The lack of teachers in managing active classes affects student learning outcomes. The purpose of this study is to improve student learning outcomes in the material for FPB and KPK through the Discovery Learning method assisted by the Dakota learning media (Dakon Mathematics). This research is a classroom action research which consists of 2 cycles, namely cycle I and cycle II. Both cycle I and cycle II have the same stages, starting from planning, implementing, observing and reflecting. The subject of the class action research was conducted at SD Negeri 3 Tanjung Ratu class VI with 26 students, 14 of whom were boys and 12 of them were girls. The object of this research is to improve student learning outcomes on the KPK and FPB materials. Data collection techniques used are tests and non-tests. The data analysis technique is comparing the percentage of student learning outcomes in cycle I and cycle II. The criteria for learning success can be seen from the increase in student learning outcomes with the application of the Discovery Learning learning method and the Dakota learning media. The results showed that the application of the Discovery Learning method and the Dakota learning media could improve student learning outcomes. The data obtained from the results of students' learning completeness in the implementation of cycle 1 with a percentage value of 47% from the previous percentage of 26% in the pre-cycle. In cycle 2 it increased to 74%..